Synthetic quartz glass preparation device for excimer laser and application of synthetic quartz glass preparation device

Through loose body deposition and sintering systems, the problem of insufficient transmittance in the ultraviolet band of synthetic quartz glass is solved, and synthetic quartz glass with high UV transmittance and low impurity content is produced, which significantly improves the performance and service life of the material.

CN119461799APending Publication Date: 2025-02-18JIANGSU HENGXIN QUARTZ TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411609342.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The insufficient transmittance of synthetic quartz glass in the ultraviolet band leads to large energy losses and service life, limiting its further application in the high-tech industry.

Method used

Using a loose body deposition and sintering system, SiO2 loose body is deposited on the rotating pallet by using a blowtorch to pass through the vaporized octamethylcyclotetrasiloxane and oxygen under a protective atmosphere, and sintered in a vacuum sintering furnace. Control the sintering temperature and atmosphere to reduce oxygen defects and impurity content.

Benefits of technology

The synthetic quartz glass produced has high UV transmittance, internal transmittance is more than 99.7%, hydroxyl, chlorine and carbon content is less than 1wt.ppm, metal impurity content is less than 10wt.ppb, stress is less than 1nm/cm, optical non-uniformity Less than 1×10-6, significantly improving the UV transparency and service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461799A_ABST
    Figure CN119461799A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of quartz synthesis, and particularly relates to a synthetic quartz glass preparation device for an excimer laser and application of the synthetic quartz glass preparation device. Comprising a loose body deposition system and a loose body sintering system; the loose body deposition system is sequentially provided with a quartz outer cavity, a quartz inner cavity with an opening in the top and a rotary quartz guide rod from outside to inside; the loose body sintering system is sequentially provided with a vacuum sintering furnace shell, a medium-frequency heating device, a quartz tube and a loose body from outside to inside; the synthesized optical element does not contain chlorine, oxygen deficiency sites and SiH groups, has extremely high ultraviolet transmittance and low absorptivity, is used for an optical system of ArF exposure equipment for transmitting ArF excimer laser, and has the refractive index uniformity [delta] n of 1 * 10 <-6 > or less, the stress birefringence amount of 1 nm / cm or less, the internal transmittance of 99.7% or more for ultraviolet rays with the wavelength of 193.4 nm, the OH group concentration of 1 ppm or less, and the refractive index uniformity [delta] n of 1 * 10 <-6 > or less. And the content of metal impurities is less than 10ppb.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of quartz synthesis, and in particular relates to a synthetic quartz glass preparation device for excimer lasers and application thereof. Background Art

[0002] Synthetic quartz glass is composed of Si and O in a molar ratio of 1:2, and the basic structural unit of the material is the [SiO4] tetrahedron. Quartz glass is an amorphous material, which means that the units in the structure are disordered, which is different from the quartz crystal formed by the orderly arrangement of [SiO4]. This material is widely used in high-tech industries such as microelectronics, precision optics, space technology and laser technology due to its high transmittance, high thermal stability, chemical stability and other high-tech industries. Among them, synthetic quartz materials with high UV transmittance are widely used in lenses and other optical accessories of precision optical devices. However, there are defects in the transmittance in the ultraviolet band, which leads to a large energy loss when the light beam passes through silica. At the same time, the absorption will be converted into heat, which affects the service life. The problem of insufficient transmittance has greatly limited the further application of synthetic quartz.

[0003] Quartz glass theoretically has high transmittance between 157 and 4000nm. However, due to the Urbach absorption edge and Rayleigh scattering, the transmittance of quartz glass is usually far from the theoretical limit. Due to impurities such as elements and groups and structural defects, the material has obvious absorption in the ultraviolet band, resulting in poor transmittance in the ultraviolet region. For synthetic quartz glass with extremely high purity, the latter is the main reason. For structural defects, point defects can be regarded as point defects in the [SiO4] tetrahedral unit, which is related to whether the atoms are bonded to each other and to which atoms they are bonded. The other is slightly larger in scale, which is related to the connection between structural units. Silicon dangling bond (E' center, Si·), consists of an ionized single oxygen vacancy and an unpaired electron. Peroxyl radical is a non-bridging superoxide ion (O2-) bonded to a single silicon atom in the glass network, (POR, SiOO·) non-bridging oxygen vacancy center Si-O·, here refers to a bond with three oxygen atoms, (·) represents an unpaired electron. Point defects can lead to absorption in the ultraviolet region. Oxygen deficiency centers (ODCs) and E' centers are caused by the absence of oxygen atoms. The former leads to absorption near 243nm, and the latter has a characteristic absorption peak position of 215nm. In the absence of hydrogen, peroxy radicals (POR), peroxy bonds, and non-bridging oxygen vacancy centers (NBOHCs) are generated. The absorption peak positions of peroxy bonds and NBOHCs are 330nm and 265nm, respectively. Hydrogen doping and fluorine doping are usually used to suppress the NBOHCs produced under laser irradiation. Hosono et al. found that the strained ring structure in the material can red-shift the ultraviolet absorption limit. At sites where the angle is far from the average, the angle Si-O-Si with a moderately reduced bonding energy can affect the VU absorption of silicon dioxide by generating near-edge localized electronic states or acting as a precursor to the color center. Koichi proposed a method to improve the vacuum ultraviolet transmittance of materials by changing point defects, and showed that F doping can effectively prevent the formation of Si-Cl and Si-OH and improve the transmittance in the VUV region.

[0004] The optical system in the lithography machine is one of its most critical and complex parts, including two core components: the illumination system and the projection objective lens. The projection objective lens is a key component for achieving precise imaging in the lithography machine. Its main function is to image the mask pattern onto the silicon wafer at a certain scale. The structure of the projection objective lens is very complex, usually composed of multiple lenses. For example, ASML's DUV lithography machine lens consists of 29 lenses, which is designed to eliminate aberrations to the greatest extent. Among them, the material of the refractive projection objective lens is mostly fused quartz. It is reported that the only manufacturers that can provide fused quartz that meets the 193nm lithography grade are Germany's Heraeus and the United States' Corning.

[0005] Since the minimum feature size of the imaging structure decreases with shorter wavelengths, modern semiconductor chips are produced using ArF excimer lasers with a wavelength of 193 nanometers (deep ultraviolet: DUV) as light sources.

[0006] The optical material selected for microlithography optics is synthetic fused silica, because it fully supports the aberration-free DUV optical system required above. Synthetic fused silica is required to have extremely high UV transmittance and low absorption. The synthetic quartz glass material used in the optical system of the ArF exposure equipment that transmits the ArF excimer laser has extremely low structural defects, its refractive index uniformity Δn is less than 1×10-6, the birefringence is less than 1nm / cm, the internal transmittance for ultraviolet light with a wavelength of 193.4nm is more than 99.7%, the OH group concentration is less than 1ppm, and the metal impurity content is less than 10ppb. Only optimized fused silica types can maintain their excellent initial performance over an expected service life of approximately 10 years.

[0007] At present, there are three methods for producing synthetic quartz:

[0008] 1. Chemical vapor deposition process (CVD)

[0009] Chemical vapor deposition refers to the deposition of silicon-containing compounds (such as SiCl4, SiH4 and Si4O4(CH3)8 and other inorganic and organic raw materials) in H2-O 2 The high temperature in the flame hydrolyzes or oxidizes to generate SiO2 particles, which are deposited layer by layer on the rotating substrate to form transparent quartz glass.

[0010] The synthetic quartz glass produced by chemical vapor deposition has low metal impurity content (<2ppm), high far ultraviolet transmittance (T185-2000nm≥85%), high optical uniformity (better than 2×10 -6 ), excellent radiation resistance (resistant to space radiation for more than 15 years), etc.; but its hydroxyl content is as high as 1200ppm, and there is a large absorption peak at 2.73μm, which affects its infrared optical properties.

[0011] 2. Plasma Chemical Vapor Deposition (PCVD)

[0012] The plasma chemical vapor deposition process refers to the use of high-purity SiCl4 as raw material, and the use of high-frequency plasma flame instead of hydrogen-oxygen flame to synthesize quartz glass in the gas phase. The quartz glass prepared by the PCVD process has low metal impurities and hydroxyl content, which makes it have excellent ultraviolet-infrared spectral transmittance, stable refractive index and high structural uniformity. In 1966, Corning Company of the United States invented a new process for producing high-purity hydroxyl-free quartz glass using high-frequency plasma. The metal impurity content is less than 5ppm, the hydroxyl content is 0-10ppm, and the chlorine content is 50-90ppm, which meets the needs of quartz glass for solar simulators, infrared tracking systems and 0.18-5μm wavelength spectrometers.

[0013] 3. Indirect synthesis method (VAD and OVD)

[0014] The indirect synthesis method is used to prepare quartz glass in contrast to the four common "direct method" technologies such as electric melting, gas refining, CVD and PCVD (quartz glass is directly obtained by heating the raw materials to a high temperature of more than 1800°C in one step). It includes two main processes: the deposition and sintering of low-density SiO2 loose bodies. That is, silicon-containing compounds (such as SiCl4, etc.) are used as raw materials, and a low-temperature chemical vapor deposition process is adopted. First, a low-density SiO2 loose body is deposited and then sintered. During the sintering process, doping, dehydration, degassing and densification are carried out simultaneously until vitrification is achieved. Since this method uses the method of hydrogen-oxygen flame hydrolysis, the loose body contains a large amount of water. If it is sintered directly, there will be a large amount of hydroxyl groups, with a hydroxyl content of 100-300ppm. It needs to be sintered in an atmosphere containing halogens, with a hydroxyl content of 1-10ppm. However, the product will have residual chloride ions, which will affect the uniformity of the product. Summary of the invention

[0015] In order to solve the above-mentioned technical problems, this application provides the following technical solutions:

[0016] The present invention provides a synthetic quartz glass preparation device for excimer laser, comprising a soot body deposition system and a soot body sintering system;

[0017] The loose body deposition system is provided with a quartz outer cavity, a quartz inner cavity with an opening at the top and a rotating quartz guide rod in sequence from the outside to the inside;

[0018] The rotating quartz guide rod is vertically arranged and can move up and down in the vertical direction, and a support plate is arranged on the top; a plurality of blowtorches are arranged on the top of the quartz outer cavity, and the blowtorches extend downward through the top of the quartz outer cavity in the vertical direction, and the distance between the bottom of the blowtorches and the support plate is 35-100mm; a vacuum device is arranged at the bottom of the quartz outer cavity; a plurality of air inlets are arranged at the bottom of the quartz inner cavity, and a plurality of exhaust ports are arranged on both sides of the quartz outer cavity;

[0019] The loose body sintering system is provided with a vacuum sintering furnace shell, a medium frequency heating device, a quartz tube and a loose body in sequence from the outside to the inside;

[0020] The shell of the vacuum sintering furnace includes a water cooling system, a cooling water inlet and an outlet; a vacuum exhaust port is also provided on the side of the shell of the vacuum sintering furnace; a vacuum pump is connected to one end of the vacuum exhaust port; the medium frequency heating device includes a metal tungsten tube and a medium frequency coil which are sequentially arranged outside the quartz tube.

[0021] Preferably, in the loose body deposition system, the air inlet and the air outlet are symmetrically arranged.

[0022] Preferably, in the loose body deposition system, a pressure gauge is also provided on the top of the quartz outer cavity.

[0023] Preferably, the loose body deposition system further comprises a pixel camera recognition device for controlling the stability of the position of the support plate.

[0024] Preferably, a nanometer filter is provided on the side of the quartz tube.

[0025] Preferably, a lower sealing plate is provided at the bottom of the quartz tube.

[0026] The present invention also provides a method for producing synthetic quartz glass for excimer lasers, using the above-mentioned synthetic quartz glass preparation device for excimer lasers, comprising the following steps:

[0027] S11: In a loose body deposition system, in a protective atmosphere, gasified octamethylcyclotetrasiloxane and oxygen are introduced through a blowtorch to start depositing a silicon dioxide loose body on a support plate; the support plate is driven to rotate by a rotating quartz guide rod, and the blowtorch and the support plate are heated to 1000-1200° C. during deposition; the heating method of the blowtorch is microwave plasma heating;

[0028] S12: pulling the rotating quartz guide rod and the supporting plate downward in the vertical direction to drive the deposited silicon dioxide loose body to descend and grow, thereby obtaining a deposited product;

[0029] S13: The silicon dioxide soot body is transferred to a quartz tube of a soot body sintering system and sintered at 1400-1600°C and 1×10 -1 After sintering for 2-4 hours at 1 Pa, the temperature is cooled to room temperature (25±5°C) to obtain synthetic quartz glass for excimer lasers.

[0030] Preferably, in the step S11, the gas pressure during heating is 5-45 Pa, and the rotation speed is 30-80 rpm; in the step S13, rotation is performed during sintering, and the rotation speed is 1-10 rpm; a medium frequency heating device is used for sintering, and the operating frequency of the medium frequency heating device is 50-2000 Hz.

[0031] Preferably, the outer diameter of the synthetic quartz glass for the excimer laser is 300-600 mm and the density is 0.5-1.2 g / cm 3 , length is 1000-2000mm.

[0032] Preferably, in the step S13, water is used to cool the furnace body of the loose body sintering system during sintering, and the surface temperature of the furnace body is controlled below 30°C.

[0033] Preferably, in step S13, water and oxygen are replaced 2-5 times before sintering, and the replacement steps are as follows:

[0034] S21: At 100-300°C, the loose body sintering system is evacuated to 0.01-0.1 Pa;

[0035] S22: Fill the loose body sintering system with helium to normal pressure (100-102 kPa), and let it stand for 15 minutes.

[0036] The optical component produced by this method has a chlorine content of less than 10wt.ppm, a hydroxyl content of less than 1wt.ppm, a carbon content of less than 1wt.ppm, a metal impurity content of less than 10wt.ppb, a glass structure with essentially no oxygen defects, no fringes in three dimensions, and an optical non-uniformity of less than 1×10 -6 , the stress is less than 1nm / cm.

[0037] The technical solution of the present invention has the following advantages over the prior art:

[0038] The synthetic quartz glass material for ArF exposure equipment of the present invention has a refractive index uniformity Δn of 1×10 -6 The stress birefringence is less than 1nm / cm, the hydroxyl, chlorine and carbon contents are less than 1wt.ppm, and the metal impurity content is less than 10wt.ppb. Synthetic quartz glass material for the optical system of ArF exposure equipment used to transmit ArF excimer laser, with an energy density range of 0.001 to 0.5mJ / cm per pulse 2 The internal transmittance for ultraviolet rays with a wavelength of 193.4nm is more than 99.7%. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a schematic diagram of loose body deposition;

[0040] Figure 2 It is a schematic diagram of the sintering of loose bodies;

[0041] Explanation of the reference numerals: 101 - blowtorch, 102 - pressure gauge, 103 - support plate, 104 - exhaust port, 105 - quartz inner cavity, 106 - quartz outer cavity, 107 - air inlet, 108 - rotating quartz guide rod, 201 - vacuum sintering furnace housing, 202 - cooling water inlet, 203 - quartz tube, 204 - vacuum exhaust port, 205 - metal tungsten tube, 206 - medium frequency coil, 207 - loose body, 208 - nanometer filter, 209 - lower sealing plate, 210 - water outlet. DETAILED DESCRIPTION

[0042] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0043] Example 1

[0044] A synthetic quartz glass preparation device for excimer laser, comprising a soot body deposition system and a soot body sintering system;

[0045] The loose body deposition system is provided with a quartz outer cavity 106, a quartz inner cavity 105 with an opening at the top and a rotating quartz guide rod 108 in sequence from the outside to the inside;

[0046] The rotating quartz guide rod 108 is vertically arranged and can move up and down in the vertical direction, and a support plate 103 is arranged on the top; a plurality of blowtorches 101 are arranged on the top of the quartz outer cavity 106, and the blowtorches 101 extend downward through the top of the quartz outer cavity 106 in the vertical direction, and the distance between the bottom of the blowtorches 101 and the support plate 103 is 35-100mm; a vacuum pump is arranged at the bottom of the quartz outer cavity 106; a plurality of air inlets 107 are arranged at the bottom of the quartz inner cavity 105, and a plurality of exhaust ports 104 are arranged on both sides of the quartz outer cavity 106; in the loose body deposition system, the air inlets 107 and the exhaust ports 104 are symmetrically arranged. In the loose body deposition system, a pressure gauge 102 is also arranged on the top of the quartz outer cavity 106. The loose body deposition system also includes a pixel camera recognition device for controlling the stability of the position of the support plate 103.

[0047] The loose body sintering system is provided with a vacuum sintering furnace shell 201, a medium frequency heating device, a quartz tube 203 and a loose body 207 in sequence from the outside to the inside;

[0048] The vacuum sintering furnace shell 201 includes a water cooling system, a cooling water inlet 202 and a water outlet 210; a vacuum exhaust port 204 is also provided on the side of the vacuum sintering furnace shell 201; one end of the vacuum exhaust port 204 is connected to a vacuum pump; the intermediate frequency heating device includes a metal tungsten tube 205 and an intermediate frequency coil 206 which are sequentially arranged outside the quartz tube 203. A nanometer filter 208 is provided on the side of the quartz tube 203, and a lower sealing plate 209 is provided at the bottom.

[0049] Example 2

[0050] The preparation system provided in this embodiment is composed of a soot body deposition system and a soot body sintering system;

[0051] The loose body deposition system includes: a raw material supply system, a reaction system, a lifting system, a control system and an exhaust system.

[0052] Raw material supply system: Octamethylcyclotetrasiloxane is used as raw material, and the raw material is gasified through an atomization device.

[0053] Reaction system: Using microwave plasma and oxygen as heat sources, an oxidation reaction occurs with octamethylcyclotetrasiloxane to produce SiO2 aerosol.

[0054] Lifting system: controls the position of the deposition surface. The position of the blowtorch 101 is fixed. As the loose bodies are deposited, the lifting system controls the loose bodies on the support plate 103 to descend.

[0055] Control system: The position of the deposition surface is identified by a pixel camera and the motor speed is controlled to keep the position of the deposition surface constant.

[0056] Exhaust system: The exhaust system discharges the undeposited SiO2 powder. At the same time, the exhaust volume is controlled by a pressure sensor to maintain a slight positive pressure inside the cavity.

[0057] The loose body sintering system includes: water cooling system, vacuum system, medium frequency heating system, workpiece melting system and filtration system.

[0058] Water cooling system: Deionized water is used to cool the furnace body, and the surface temperature of the furnace body is controlled below 30°C.

[0059] Vacuum system: Use a vacuum pump to create negative pressure inside the furnace cavity, with a pressure range of 1 to 10 -4 pa.

[0060] Medium frequency heating system: The operating frequency of the medium frequency induction furnace is between 50-2000Hz, and the temperature range is 1200-1800℃.

[0061] Workpiece melting system: The workpiece melting is carried out inside a closed quartz tube, and the sintering temperature is 1200-1800℃.

[0062] Filtration system: A nanometer filter 208 is used to discharge the gas inside the quartz tube and prevent external impurities from entering the inside of the quartz tube.

[0063] Example 3

[0064] A method for producing synthetic quartz glass for excimer lasers, using the preparation system of Example 1, the process steps are as follows:

[0065] 1. Deposition preparation: the motor drives the spindle to rotate at a speed of 50 rpm, and the quartz substrate is heated to 1200°C through the plasma heat source; at the same time, dry protective gas is introduced into the air inlet 107 to keep the cavity at a slightly positive pressure of 5 Pa.

[0066] 2. Feeding deposition: Octamethylcyclotetrasiloxane and oxygen are introduced into a blowtorch 101 heated to 1200°C to deposit SiO2 loose bodies on a quartz substrate (i.e., a support plate 103); the distance between the blowtorch 101 and the quartz substrate is 35 mm;

[0067] 3. Sedimentation control: the loose body is driven down by the lifting device; the deposition surface is controlled to remain constant by the pixel camera;

[0068] 4. After the product is transferred and reaches the set length, the loose body is taken out and prepared for sintering. The transfer device is protected by gas, and the water content of the protective gas is less than 1wt.ppm.

[0069] 5. Product sintering installation: install the product into the quartz tube 203 of the loose body sintering system at a rotation speed of 5 rpm;

[0070] 6. Low temperature vacuuming: vacuuming at 200°C, with a negative pressure of 0.05Pa in the cavity;

[0071] 7. Gas replacement: slowly fill the vacuum furnace with dry He until it is at normal pressure and then stand for 15 minutes;

[0072] 8. Repeat steps 6 and 7 twice;

[0073] 9. High temperature vacuuming, using a medium frequency induction furnace with an operating frequency of 1000Hz, a temperature of 1500℃, a cavity negative pressure of 1Pa, and constant temperature and pressure for 3 hours;

[0074] 10. Take the material, cool it down to room temperature, take out the material, and the operation is completed.

[0075] Example 4

[0076] A method for producing synthetic quartz glass for excimer lasers, using the preparation system of Example 1, the process steps are as follows:

[0077] 1. Deposition preparation: The motor drives the spindle to rotate at a speed of 50 rpm. The quartz substrate is heated to 1200°C through a plasma heat source. At the same time, dry protective gas is introduced into the air inlet 107 to keep the cavity at a slightly positive pressure of 15 Pa.

[0078] 2. Feeding deposition: Octamethylcyclotetrasiloxane and oxygen are introduced into the blowtorch 101 heated to 1200°C to deposit SiO2 loose bodies on the quartz substrate (i.e., the support plate 103); the distance between the blowtorch 101 and the quartz substrate is 50 mm;

[0079] 3. Sedimentation control: the loose body is driven down by the lifting device; the deposition surface is controlled to remain constant by the pixel camera;

[0080] 4. After the product is transferred and reaches the set length, the loose body is taken out and prepared for sintering. The transfer device is protected by gas, and the water content of the protective gas is less than 1wt.ppm.

[0081] 5. Product sintering installation: install the product into the quartz tube 203 of the loose body sintering system at a rotation speed of 5 rpm;

[0082] 6. Low temperature vacuuming: vacuuming at 200°C, with a negative pressure of 0.05Pa in the cavity;

[0083] 7. Gas replacement: slowly fill the vacuum furnace with dry He until it is at normal pressure and then stand for 15 minutes;

[0084] 8. Repeat steps 6 and 7 twice;

[0085] 9. High temperature vacuuming, using a medium frequency induction furnace with an operating frequency of 1000Hz, a temperature of 1500℃, a cavity negative pressure of 0Pa, and constant temperature and pressure for 3 hours;

[0086] 10. Take the material, cool it down to room temperature, take out the material, and the operation is completed.

[0087] Example 5

[0088] A method for producing synthetic quartz glass for excimer lasers, using the preparation system of Example 1, the process steps are as follows:

[0089] 1. Deposition preparation: the motor drives the spindle to rotate at a speed of 50 rpm, and the quartz substrate is heated to 1200°C through the plasma heat source; at the same time, dry protective gas is introduced into the air inlet 107 to keep the cavity at a slightly positive pressure of 25 Pa.

[0090] 2. Feeding deposition: Octamethylcyclotetrasiloxane and oxygen are introduced into the blowtorch 101 heated to 1200°C to deposit SiO2 loose bodies on the quartz substrate (i.e., the support plate 103); the distance between the blowtorch 101 and the quartz substrate is 65 mm;

[0091] 3. Sedimentation control: the loose body is driven down by the lifting device; the deposition surface is controlled to remain constant by the pixel camera;

[0092] 4. After the product is transferred and reaches the set length, the loose body is taken out and prepared for sintering. The transfer device is protected by gas, and the water content of the protective gas is less than 1wt.ppm.

[0093] 5. Product sintering installation: install the product into the quartz tube 203 of the loose body sintering system at a rotation speed of 5 rpm;

[0094] 6. Low temperature vacuuming: vacuuming at 200°C, with a negative pressure of 0.05Pa in the cavity;

[0095] 7. Gas replacement: slowly fill the vacuum furnace with dry He until it is at normal pressure and then stand for 15 minutes;

[0096] 8. Repeat steps 6 and 7 twice;

[0097] 9. High temperature vacuuming, using a medium frequency induction furnace with an operating frequency of 1000Hz, a temperature of 1500℃, a cavity negative pressure of 0.5Pa, and constant temperature and pressure for 3 hours;

[0098] 10. Take the material, cool it down to room temperature, take out the material, and the operation is completed.

[0099] Example 6

[0100] A method for producing synthetic quartz glass for excimer lasers, using the preparation system of Example 1, the process steps are as follows:

[0101] 1. Deposition preparation: the motor drives the spindle to rotate at a speed of 50 rpm, and the quartz substrate is heated to 1200°C through the plasma heat source; at the same time, dry protective gas is introduced into the air inlet 107 to keep the cavity at a slightly positive pressure of 35 Pa.

[0102] 2. Feeding deposition: Octamethylcyclotetrasiloxane and oxygen are introduced into the blowtorch 101 heated to 1200°C to deposit SiO2 loose bodies on the quartz substrate (i.e., the support plate 103); the distance between the blowtorch 101 and the quartz substrate is 80 mm;

[0103] 3. Sedimentation control: the loose body is driven down by the lifting device; the deposition surface is controlled to remain constant by the pixel camera;

[0104] 4. After the product is transferred and reaches the set length, the loose body is taken out and prepared for sintering. The transfer device is protected by gas, and the water content of the protective gas is less than 1wt.ppm.

[0105] 5. Product sintering installation: install the product into the quartz tube 203 of the loose body sintering system at a rotation speed of 5 rpm;

[0106] 6. Low temperature vacuuming: vacuuming at 200°C, with a negative pressure of 0.05Pa in the cavity;

[0107] 7. Gas replacement: slowly fill the vacuum furnace with dry He until it is at normal pressure and then stand for 15 minutes;

[0108] 8. Repeat steps 6 and 7 twice;

[0109] 9. High temperature vacuuming, using a medium frequency induction furnace with an operating frequency of 1000Hz, a temperature of 1500℃, a cavity negative pressure of 0.1Pa, and constant temperature and pressure for 3 hours;

[0110] 10. Take the material, cool it down to room temperature, take out the material, and the operation is completed.

[0111] Table 1 Performance characteristics of synthetic quartz glass for excimer lasers in Examples 3 to 6

[0112]

[0113] Example 7

[0114] A method for producing synthetic quartz glass for excimer lasers, using the preparation system of Example 1, the process steps are as follows:

[0115] 1. Deposition preparation: the motor drives the spindle to rotate at a speed of 30 rpm, and the quartz substrate is heated to 1000°C through the plasma heat source; at the same time, dry protective gas is introduced into the air inlet 107 to keep the cavity at a slightly positive pressure of 5 Pa.

[0116] 2. Feeding and deposition: Octamethylcyclotetrasiloxane and oxygen are introduced into a blowtorch 101 heated to 1000°C to deposit SiO2 loose bodies on a quartz substrate (i.e., a support plate 103);

[0117] 3. Sedimentation control: the loose body is driven down by the lifting device; the deposition surface is controlled to remain constant by the pixel camera;

[0118] 4. After the product is transferred and reaches the set length, the loose body is taken out and prepared for sintering. The transfer device is protected by gas, and the water content of the protective gas is less than 1wt.ppm.

[0119] 5. Product sintering installation: install the product into the quartz tube 203 of the loose body sintering system at a rotation speed of 1 rpm;

[0120] 6. Low temperature vacuuming: vacuuming at 100℃, with negative pressure of 10 -1 pa;

[0121] 7. Gas replacement: slowly fill the vacuum furnace with dry He until it is at normal pressure and then stand for 15 minutes;

[0122] 8. Repeat steps 6 and 7 twice;

[0123] 9. High temperature vacuuming, using a medium frequency induction furnace with an operating frequency of 50Hz, a temperature of 1400℃, a cavity negative pressure of 1pa, and constant temperature and pressure for 2 hours;

[0124] 10. Take the material, cool it down to room temperature, take out the material, and the operation is completed.

[0125] Example 8

[0126] A method for producing synthetic quartz glass for excimer lasers, using the preparation system of Example 1, the process steps are as follows:

[0127] 1. Deposition preparation: the motor drives the spindle to rotate at a speed of 80 rpm, and the quartz substrate is heated to 1200°C through the plasma heat source; at the same time, dry protective gas is introduced into the air inlet 107 to keep the cavity at a slightly positive pressure of 45 Pa.

[0128] 2. Feeding and deposition: Octamethylcyclotetrasiloxane and oxygen are introduced into the blowtorch 101 heated to 1200°C to deposit SiO2 loose bodies on the quartz substrate (i.e., the support plate 103);

[0129] 3. Sedimentation control: the loose body is driven down by the lifting device; the deposition surface is controlled to remain constant by the pixel camera;

[0130] 4. After the product is transferred and reaches the set length, the loose body is taken out and prepared for sintering. The transfer device is protected by gas, and the water content of the protective gas is less than 1wt.ppm.

[0131] 5. Product sintering installation: install the product into the quartz tube 203 of the loose body sintering system at a rotation speed of 10 rpm;

[0132] 6. Low temperature vacuuming: vacuuming at 300℃, with negative pressure of 10 -2 pa;

[0133] 7. Gas replacement: slowly fill the vacuum furnace with dry He until it is at normal pressure and then stand for 15 minutes;

[0134] 8. Repeat steps 6 and 7 5 times;

[0135] 9. High temperature vacuum, use medium frequency induction furnace with working frequency of 2000Hz, temperature of 1600℃, cavity negative pressure of 10 -1 pa, constant temperature and pressure for 4 hours;

[0136] 10. Take the material, cool it down to room temperature, take out the material, and the operation is completed.

[0137] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A synthetic quartz glass preparation device for excimer laser, characterized in that: It includes a soot body deposition system and a soot body sintering system; The loose body deposition system is provided with a quartz outer cavity (106), a quartz inner cavity (105) with an opening at the top, and a rotating quartz guide rod (108) in sequence from the outside to the inside; The rotating quartz guide rod (108) is vertically arranged and can move up and down in the vertical direction, and a support plate (103) is arranged on the top; a plurality of blowtorches (101) are arranged on the top of the quartz outer cavity (106), and the blowtorches (101) extend downward through the top of the quartz outer cavity (106) in the vertical direction, and the distance between the bottom of the blowtorches (101) and the support plate (103) is 35-100 mm; a vacuum device is arranged at the bottom of the quartz outer cavity (106); a plurality of air inlets (107) are arranged at the bottom of the quartz inner cavity (105), and a plurality of air outlets (104) are arranged on both sides of the quartz outer cavity (106); The loose body sintering system is provided with a vacuum sintering furnace shell (201), a medium frequency heating device, a quartz tube (203) and a loose body (207) in sequence from the outside to the inside; The vacuum sintering furnace shell (201) comprises a water cooling system, a cooling water inlet (202) and a cooling water outlet (210); a vacuum exhaust port (204) is also provided on the side of the vacuum sintering furnace shell (201); one end of the vacuum exhaust port (204) is connected to a vacuum pump; the medium frequency heating device comprises a metal tungsten tube (205) and a medium frequency coil (206) which are sequentially arranged outside the quartz tube (203).

2. The synthetic quartz glass preparation device for excimer laser according to claim 1, characterized in that: In the loose body deposition system, the air inlet (107) and the air outlet (104) are both symmetrically arranged.

3. The synthetic quartz glass preparation device for excimer laser according to claim 1, characterized in that: In the loose body deposition system, a pressure gauge (102) is also provided on the top of the quartz outer cavity (106).

4. The synthetic quartz glass preparation device for excimer laser according to claim 1, characterized in that: The loose body deposition system further comprises a pixel camera recognition device for controlling the position stability of the support plate (103).

5. The synthetic quartz glass preparation device for excimer laser according to claim 1, characterized in that: A nanometer filter (208) is provided on the side of the quartz tube (203).

6. A method for producing synthetic quartz glass for excimer laser, characterized in that: The synthetic quartz glass preparation device for excimer laser according to any one of claims 1 to 5 comprises the following steps: S11: In a loose body deposition system, in a protective atmosphere, gasified octamethylcyclotetrasiloxane and oxygen are introduced through a blowtorch (101) to start depositing a silicon dioxide loose body on a support plate (103); the support plate (103) is driven to rotate by a rotating quartz guide rod (108), and the blowtorch (101) and the support plate (103) are heated to 1000-1200° C. during deposition; the heating method of the blowtorch (101) is microwave plasma heating; S12: Pulling the rotating quartz guide rod (108) and the support plate (103) downward in a vertical direction to drive the deposited silicon dioxide loose body to descend and grow, thereby obtaining a deposited product; S13: The silicon dioxide soot body is transferred to a quartz tube (203) of a soot body sintering system and heated at 1400-1600°C and 1×10 -1 After sintering for 2-4 hours under ~1Pa conditions and then cooling to room temperature, synthetic quartz glass for excimer lasers is obtained.

7. The method for producing synthetic quartz glass for excimer laser according to claim 6, characterized in that: In the step S11, the gas pressure during heating is 5-45 Pa, and the rotation speed is 30-80 rpm; in the step S13, rotation is performed during sintering, and the rotation speed is 1-10 rpm; a medium frequency heating device is used for sintering, and the operating frequency of the medium frequency heating device is 50-2000 Hz.

8. The method for producing synthetic quartz glass for excimer laser according to claim 6, characterized in that: The synthetic quartz glass for excimer laser has an outer diameter of 300-600 mm and a density of 0.5-1.2 g / cm 3 , length is 1000-2000mm.

9. The method for producing synthetic quartz glass for excimer laser according to claim 6, characterized in that: In the step S13, water is used to cool the furnace body of the loose body sintering system during sintering, and the surface temperature of the furnace body is controlled below 30°C.

10. The method for producing synthetic quartz glass for excimer laser according to claim 6, characterized in that: In step S13, water and oxygen are replaced 2-5 times before sintering, and the replacement steps are as follows: S21: At 100-300°C, the loose body sintering system is evacuated to 0.01-0.1 Pa; S22: Fill the loose body sintering system with helium to normal pressure and let it stand for 15 minutes.